Compliance with Health Recommendations and Vaccine Hesitancy During the COVID Pandemic in Nine Countries - Lansford, Jennifer E (Archīum Ateneo, 2022)
Longitudinal data from the Parenting Across Cultures study of children, mothers, and fathers in 12 cultural groups in nine countries (China, Colombia, Italy, Jordan, Kenya, the Philippines, Sweden, Thailand, and the USA; N = 1331 families) were used to understand predictors of compliance with COVID-19 mitigation strategies and vaccine hesitancy. Confidence in government responses to the COVID pandemic was also examined as a potential moderator of links between pre-COVID risk factors and compliance with COVID mitigation strategies and vaccine hesitancy. Greater confidence in government responses to the COVID pandemic was associated with greater compliance with COVID mitigation strategies and less vaccine hesitancy across cultures and reporters. Pre-COVID financial strain and family stress were less consistent predictors of compliance with COVID mitigation strategies and vaccine hesitancy than confidence in government responses to the pandemic. Findings suggest the importance of bolstering confidence in government responses to future human ecosystem disruptions, perhaps through consistent, clear, non-partisan messaging and transparency in acknowledging limitations and admitting mistakes to inspire compliance with government and public health recommendations.